Adenosine A1 receptors modulate the Na+-Hypertonicity induced glutamate release in hypothalamic glial cells. (June 2019) - Braga, Danielle Valente; Wanderley Picanço-Diniz, Domingos Luiz; Herculano Matos Oliveira, Karen Renata; Luz, Waldo Lucas; Soares de Moraes, Suellen Alessandra; Fonseca Passos, Adelaide C.; de Jesus Oliveira Batista, Evander; Grisólia, Alan; Herculano, Anderson Manoel
Abstract: Glutamate release in response to a hypertonic stimulus is a well described phenomenon in the hypothalamus. Evidence suggests that hypothalamic glial cells release glutamate into the extracellular environment in hypertonic conditions. In the current study, we described autocrine regulation of adenosine on glutamate release induced by Na + hypertonicity in hypothalamic glial cell cultures. We showed that glial cells cultured from the cerebral cortex did not release glutamate or adenosine under hypertonic conditions. The findings suggest that the hypothalamus has specialized glial cells, which are responsive to osmotic variations. Stimulation or inhibition of adenosine A1 receptors modulates extracellular glutamate levels in hypothalamic glial cell cultures under hypertonic stimulation. Our results extend previous observations regarding the role of glial cells in the control of hypothalamic physiology. They further demonstrate for the first time that hypothalamic glial cells regulate Na + -hypertonicity-induced glutamate release by activation of adenosine A1 receptors via adenosine release. Graphical abstract: Neurochemical response of brain glial and hypothalamic glial cells response to hypertonic stimulus. (A) Brain cortex glial cells do not release glutamate or adenosine in response to hypertonic stimulation. (B) However, hypothalamic glial cells release adenosine and glutamate in response to hypertonic stimulation and adenosine activates adenosine A1 receptors which dowregulates glial glutamate release induced by Na + -hypertonicity.Image 1 Highlights: Hypertonicity induces glutamate and adenosine release from hypothalamic glial cells. Hypothalamic glial cells under hypertonic stimulus autoregulate their glutamate release. Adenosine regulates glutamate release induced by hypertonicity in hypothalamic glial cells. Adenosine A1 receptors modulates glutamate release in hypothalamic glial cells.